Cell-Free DNA Sequencing of Intraocular Fluid as Liquid Biopsy in the Diagnosis of Vitreoretinal Lymphoma - Gu, Junxiang; Jiang, Tingting; Liu, Shixue; Ping, Bo; Li, Ruiwen; Chen, Wenwen; Wang, Ling; Huang, Xin; Xu, Gezhi; Chang, Qing (Frontiers in Oncology, 2022)
Purpose To seek novel diagnostic approaches, we improved the workflow of cell-free DNA (cfDNA) sequencing and evaluated its feasibility in vitreoretinal lymphoma (VRL) specimens; the profile of mutations was preliminarily analyzed for potential diagnostic value. Methods The study was a diagnostic trial. 23 eyes of 23 patients with VRL and 25 eyes of 25 patients with inflammatory eye diseases were enrolled. Approximate 500μl undiluted vitreous humor and 10ml diluted vitreous fluid was obtained through diagnostic vitrectomy and sent for cytopathological examinations. 500μl of the diluted vitreous fluid was spared for cfDNA sequencing. For cfDNA sequencing, DNA fragmentation procedure was added to the workflow to improve the extraction efficiency; mutations detected were analyzed for potential diagnostic model. The sensitivity and specificity of the cytopathology and cfDNA sequencing were compared. The clinical manifestations were preliminarily analyzed for potential correlations with the genotypes. Results CfDNA sequencing was accomplished in 23 eyes with VRL and 20 eyes with inflammatory eye diseases. VRL-related mutated genes included MYD88 (18 eyes, 78%), ETV6 (11 eyes, 48%), PIM1 (11 eyes,48%), BTG2 (7 eyes, 30%), IRF4 (7 eyes, 30%), CD79B (6 eyes, 26%), LRP1B (6 eyes, 26%), etc. Logistic regression based on the mutations of MYD88 and ETV6 was of the potential for the diagnosis of VRL (P<0.001, adjusted R2 = 0.789, sensitivity 0.913, specificity 0.950); by comparison, the sensitivity and specificity of the vitreous cytopathology were 0.826 and 1.000, respectively. Further analysis of the mutation profile showed that patients carrying CD79B mutation tended to have higher intraocular interleukin-10 level (P=0.030), that CARD11 mutation was correlated with younger age at ocular onset (P=0.039), and that patients with intracranial involvement carried more multiple-site mutations in the BTG2 gene (P=0.013). Conclusions The improved workflow of CfDNA sequencing is of sound feasibility in a limited amount of vitreous humor. The logistic model based on the mutations could help to provide reliable clues for the diagnosis of VRL.